Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/biomedicines10112743
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Oral Pterostilbene in Multistage Carcinogenesis of Skin Squamous Cell Carcinoma Mouse Model Induced by DMBA/TPA

Abstract: Skin squamous cell carcinoma (SCC) is a type of non-melanoma skin cancer. Pterostilbene is a natural compound proven to exhibit various pharmacological properties, including chemo-preventive effects. This study aimed to explore the chemo-preventive effect of oral pterostilbene during initiation, promotion or continuous on multistage skin SCC mouse models induced by 7,12-Dimethylbenz(a)anthracene (DMBA)/12-O-Tetradecanoylphorbol-13-acetate (TPA). The experimental design consists of five groups of female Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The study aimed to investigate the anti-cancer activity of CKE against DMBA/TPA-induced skin SCC by protecting cellular mechanisms like reducing oxidative stress and suppressing c-MYC gene expression. SSC, a subtype of NMSC, is the second most prevalent cancer in the world and is distinguished by abnormal keratinocyte proliferation [ 2 , 82 ]. More significantly, the Indian subcontinent has a higher prevalence of SCC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed to investigate the anti-cancer activity of CKE against DMBA/TPA-induced skin SCC by protecting cellular mechanisms like reducing oxidative stress and suppressing c-MYC gene expression. SSC, a subtype of NMSC, is the second most prevalent cancer in the world and is distinguished by abnormal keratinocyte proliferation [ 2 , 82 ]. More significantly, the Indian subcontinent has a higher prevalence of SCC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirmed PTR’s antioxidant properties through both in vitro and in vivo experiments, demonstrating its preventive and therapeutic potential. PTR’s antioxidant capabilities have been associated with its role in preventing cancer, influencing neurological conditions, reducing inflammation, mitigating vascular diseases, and improving diabetes outcomes [ 2 , 21 , 39 ]. Moreover, the in silico study of PTR activity has been of interest in various biomedical applications [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The broad spectrum of biological activity of pterostilbene suggests that this compound may have a preventive and therapeutic effect on malignant melanoma. To date, there are only a few reports on the biological activity of pterostilbene in melanoma cells and the mechanism by which pterostilbene can exert potential anticancer effects on skin cancers [ 18 ]. Most anticancer drugs exert their biological activity by inhibition of the cell cycle and induction of programmed cell death, such as apoptosis, autophagy, and necroptosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%